Perencanaan Penjadwalan Perawatan Preventif Pada Mesin Duplex di Pabrik Kertas - Ganjar Setiaji; Johan K Runtuk (President University, 2018)
Maintenance is an important activity in ensuring the machine operation in a company. If maintenance activities are carried out in a planned manner, production activities can run smoothly. This research was conducted in a manufacturing company engaged in the manufacture of paper packaging. Based on the data, Duplex machines have a higher frequency of breakdown compared to other machines, which is 125 times in 22 months. This study aims to implement preventive maintenance of Duplex machines. The analysis starts with determining the critical components on a Duplex machine. Furthermore, the calculation of Mean Time to Failure (MTTF), Cost of Failure (Cf), and reliability. Finally, a preventive maintenance cost calculation (Cp) was carried out to determine the time interval for replacing components at a low cost. After the implementation of preventive maintenance, there were three components that experienced a decrease in maintenance costs. Bearing components experience a cost reduction of 8.30% with a reliability of 61%, chain components have decreased costs by 15.60% with a reliability of 62% and unwinder components have decreased costs by 10.70% with a reliability of 61%.Keywords: Duplex machine, preventive maintenance, MTTF, reliability